Digitalisasi Sistem Informasi Perpustakaan pada MI Hidayatul Ulum - Nafis Sururi; Fendy Bayu Firmansyah; Danang Satya Nugraha; Zamilu Toniatul Mina; Muh Fahrizal A (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
This community service activity was motivated by the need for an efficient and structured library management system at MI Hidayatul Ulum. Previously, book recording, borrowing, and reporting were done manually, creating administrative challenges and limiting access to information for students and teachers. To address these challenges, the community service team implemented a web-based library information system designed to simplify collection management, facilitate book searches, and expedite the borrowing and return process. The implementation method included partner needs analysis, system design and installation, training for staff and teachers, and evaluation of implementation results. The system was designed to be accessible through the school's local network with a simple and user-friendly interface. Training was provided to ensure the school was able to utilize and manage the system independently. The results showed that the implementation of this information system improved library management efficiency and expanded user access to information. Teachers could more easily monitor book collections, while students found it easier to search for and borrow books. Furthermore, the system accelerated administrative processes and reduced the risk of recording errors. Another positive impact was the growth of a technology-based literacy culture within the madrasah. With the availability of faster book search and borrowing services, students' interest in reading increased. A participatory approach involving schools from the planning stage through evaluation ensures that the resulting solutions meet needs and can be implemented sustainably. This community service activity is expected to serve as a model for implementing simple technology that has a real impact on improving the quality of basic education services.